8 IS ENDOSCOPY NECESSARY FOR THE MEASUREMENT OF DISEASE ACTIVITY IN ULCERATIVE COLITIS?. (1st March 2005) - Higgins, P. D.R.; Schwartz, M.; Mapili, J.; Zimmermann, E. M.
Abstract : Objectives: Many disease activity indices are used to measure ulcerative colitis. Invasive indices incorporate an endoscopic score, while noninvasive indices do not require endoscopy. In clinical practice, many patients are treated based on their symptoms without endoscopic evaluation. However, invasive indices are commonly used in clinical research. Our objective was to determine whether endoscopy is necessary for the assessment of disease activity in patients with ulcerative colitis. Methods: Sixty-six consecutive ulcerative colitis patients were evaluated with invasive indices: the St. Mark's index, and the Ulcerative Colitis Disease Activity Index (UCDAI); and noninvasive indices: the Simple Clinical Colitis Activity Index (SCCAI), and the Seo index. The correlations between the indices were measured. The contribution of the endoscopic items was measured with linear regression modeling. The overlap of endoscopy with other items in the standard indices was determined through factor analysis. Results: The two noninvasive indices correlated well with the invasive St. Mark's Index (SCCAI 0.86, Seo 0.70). After adjusting for the three noninvasive UCDAI items, the UCDAI endoscopy item predicted only 0.04% of the variance in the St. Mark's index. Factor analysis demonstrated that this is because the endoscopy items in the invasive indices correlate with stool frequency and stool blood items. Conclusions: Endoscopy items contribute little additional information to indices of disease activity in ulcerative colitis. The clinical practice of treating patients based on reported symptoms is appropriate. The use of noninvasive indices in clinical trials could lower study costs and may increase subjects' willingness to participate.